The Gender Question in Amoris Laetitia. Approach to a Complex Subject - Mazzini, Marcela (Teología, 2020)
This text analyzes how the issue of Gender appears in Amoris Laetitia. Based on the concept of the family he uses, it analyzes the text and problematizes the reception of the exhortation in our country. The article ends by raising the topic of the place of women in the Church and takes the meeting of women from popular neighborhoods that took place on June 20, 2019, as an inspiring event for a more incisive presence of women in the Church.